Does Corporate Governance Matter for Audit Quality? Evidence from Sri Lanka - Pratheepkanth, P.; Rajumesh, S. (Universiti Teknologi MARA, Malaysia, 2022)
This study aimed to investigate the effects of corporate governance on audit quality. Using a sample of 100 Sri Lankan listed companies from 2016 to 2020, this study used the ordinary least squares method. The results of this study overall suggests that there is a significant relationship between board size, board independence, audit committee independence and audit quality proxies. However, CEO duality and audit committee financial literacy are only significantly associated with BIG4. This study demonstrates the need of taking the institutional context into account in governance studies. This research focused on companies in Sri Lanka. Future studies should look into this issue in other contexts and time periods. This study is significant for practitioners and academics, legislators, and professional accounting organisations because it demonstrates how legislative reforms might encourage corporations in emerging markets to adopt good governance practices. The findings are also valuable for investors in examining the impact of corporate governance on audit quality. The study adds to the body of knowledge by demonstrating that there is a substantial association between corporate governance and audit quality in Sri Lankan listed companies.
Keywords: Corporate Governance; Audit Quality; Sri Lanka